Assessing the impact of socio‐economic determinants on access to care, surgical treatment options and outcomes among patients with renal mass: Insight from the universal healthcare system. (22nd July 2022) - Grosso, Antonio Andrea; Di Maida, Fabrizio; Tellini, Riccardo; Viola, Lorenzo; Lambertini, Luca; Valastro, Francesca; Mari, Andrea; Masieri, Lorenzo; Carini, Marco; Minervini, Andrea
Abstract: Objective: To assess whether socio‐economic disparities exist on access to care, treatment options and outcomes among patients with renal mass amenable of surgical treatment within the universal healthcare system. Methods: Data of consecutive patients submitted to partial nephrectomy (PN) or radical nephrectomy (RN) at our Institution between 2017 and 2020 were retrospectively evaluated. Patients were grouped according to their income level (low, intermediate, and high) based on the Indicator of Equivalent Economic Situation national criterion. Survival analysis was performed. Cox regression models were employed to analyse the impact of socio‐economic variables on survival outcomes. Results: One thousand forty‐two patients were included (841 PN and 201 RN). Patients at the lowest income level were found more likely symptomatic and with a higher pathological tumour stage in the RN cohort ( p > 0.05). The guidelines adherence on surgical indication rate as well as the access to minimally invasive surgery did not differ according to patient's income level in both cohorts ( p > 0.05). Survival curves were comparable among the groups. Cox regression analysis showed that none of the included socio‐economic variables was associated with survival outcomes in our series. Conclusions: Universal healthcare system may increase the possibility to ensure egalitarian treatment modalities for patients with renal cancer.